The roles of COX-2 in protozoan infection - Wang, Xinlei; Chen, Jie; Zheng, Jingtong (Frontiers in Immunology, 2023)
Protozoan diseases cause great harm in animal husbandry and require human-provided medical treatment. Protozoan infection can induce changes in cyclooxygenase-2 (COX-2) expression. The role played by COX-2 in the response to protozoan infection is complex. COX-2 induces and regulates inflammation by promoting the synthesis of different prostaglandins (PGs), which exhibit a variety of biological activities and participate in pathophysiological processes in the body in a variety of ways. This review explains the roles played by COX-2 in protozoan infection and analyzes the effects of COX-2-related drugs in protozoan diseases.